204k views
10 votes
Which of the answers are correct? there is possibly more than one.

Which of the answers are correct? there is possibly more than one.-example-1

1 Answer

6 votes

Answer:


b_2 = (2A)/(h) -b_1

Explanation:

Given


A = (1)/(2)h(b_1 + b_2)

Required

Select equivalent expressions

Multiply through by 2


2*A = 2*(1)/(2)h(b_1 + b_2)


2*A = h(b_1 + b_2)


2A = h(b_1 + b_2)

Divide through by h


(2A)/(h) = (h(b_1 + b_2))/(h)


(2A)/(h) = b_1 + b_2

Subtract b1 from both sides


(2A)/(h) -b_1= -b_1 + b_1 + b_2


(2A)/(h) -b_1= b_2


b_2 = (2A)/(h) -b_1

From the list of options, there is only one answer

User JongHyeon Yeo
by
5.3k points